Influence of PMSG on Superstimulation and Embryo Development Following Somatic Cell Nuclear Transfer in Holstein Cows in the United Arab Emirates - Son, Young-Bum; Jeong, Yeon Ik; Hossein, Mohammad Shamim; Yu, Xianfeng; Olsson, Per Olof; Kang, Mina; Kim, Huijeong; Bae, Yura; Tinson, Alex; Singh, Kuhad Kuldip; Rajesh, Singh; Noura, Al Shamsi; et al. (Frontiers in Veterinary Science, 2022)
The present study investigated the effect of superstimulation to improve in vitro embryo production in the Gulf area, where the temperature is high. Holstein cows were classified into the control and superstimulation groups. Superstimulation was induced with a single intramuscular injection of pregnant mare serum gonadotropin (PMSG; 2500 IU) on day 14 of the estrus cycle (day 0; estrus). The development of follicles was evaluated by ultrasonography of the ovaries daily. At 40 h after the PMSG injection, oocytes were collected by the ovum pick-up (OPU) technique. OPU was performed at the same stage of the estrus cycle in the control group as in the superstimulation group. The number of follicles with a diameter of more than 6 mm and the number of retrieved cumulus-oocyte complexes were significantly higher in the superstimulation group than in the control group. Furthermore, the maturation rate was higher in the superstimulation group than in the control group. Cloned embryos were produced by somatic cell nuclear transfer using matured oocytes. The cleavage and blastocyst formation rates were significantly higher in the superstimulation group than in the control group. In conclusion, a single injection of PMSG can facilitate the efficient production of cloned cow embryos.